Playing the game: ethnicity and politics in Indonesian badminton - Brown, Colin (2006)
The scholarly study of sport--in which "sports are viewed as cultural products that develop within sociohistorical contexts" --is now well-established. However, the literature suffers from two important and related defects. One of these defects is its geographical focus. As van Bottenburg notes in his study, Global Games, the scholarly literature on sport "is mainly limited to developments in the Western world. Information on the other continents is at best fragmentary, often collected in wide-ranging surveys." In particular, relatively little has been written on sport and politics in the Asian context.This study, albeit preliminary, shows that badminton--and sport generally, perhaps--deserves closer attention by students of Indonesian social history than has been the case thus far. In badminton, Indonesians found a competitive sport in which, for most of the past half century, their athletes could figure as world champions. Closer examination of the meaning of badminton to Indonesians is necessary for confirmation, but evidence from this study suggests that the game was important in the way it reinforced a sense of Indonesian national identity and worth in the world.